Regional financing arrangements and the stability of the international monetary system - Julie MacKay; Ulrich Volz; Regine Wölfinger (Deutsches Institut für Entwicklungspolitik (DIE), 2010)
Developments in regional financing arrangements, such as the strengthening of the Chiang Mai Initiative in East Asia, and the increased lending in the global financial crisis are increasingly raising questions about their contribution to the stability of the international financial system, and their relation to the International Monetary Fund (IMF) and its role in safeguarding that stability. Key questions concern the implications of regional financing arrangements for the lending and surveillance functions of the IMF and whether they could come to supplant Fund financing. Indeed, emerging market interest in regional financing arrangements may be attributed to perceptions of an undue burden of conditionality attached to IMF lending, and the dissatisfaction expressed by larger, dynamic emerging market economies over their lack of influence in the Fund's decision-making, as evident in their calls for representation commensurate with their economic significance. This issue has not yet been squarely addressed, and this paper seeks to fill that gap. It explores the argument that the contribution of regional financing arrangements to the stability of the international monetary and financial system depends on their design and operation. To gauge the quality of a regional financing arrangement, we establish a set of critical factors – “optimal financing criteria” – relevant for providing crisis financing, using a first principles approach. We then evaluate the frameworks for the IMF and the various regional arrangements in existence against these criteria. Results suggest that the design and operation of regional arrangements determine whether the extent to which they help alleviate crises. In essence, we find that those in existence can be expected to have superior information about the economy in crisis, and react more quickly to address a situation, but may lack the expertise to define the policy course towards external sustainability and the amount of funding necessary to reassure markets.
Keywords: 330